Effects of host and pathogenicity on mutation rates in avian influenza A viruses. Issue 1 (21st February 2022) - Kim, Gwanghun; Shin, Hyun Mu; Kim, Hang-Rae; Kim, Yuseob
Abstract: Mutation is the primary determinant of genetic diversity in influenza viruses. The rate of mutation, measured in an absolute time-scale, is likely to be dependent on the rate of errors in copying RNA sequences per replication and the number of replications per unit time. Conditions for viral replication are probably different among host taxa, potentially generating the host specificity of the viral mutation rate, and possibly between highly and low pathogenic (HP and LP) viruses. This study investigated whether mutation rates per year in avian influenza A viruses depend on host taxa and pathogenicity. We inferred mutation rates from the rates of synonymous substitutions, which are assumed to be neutral and thus equal to mutation rates, at four segments that code internal viral proteins (PB2, PB1, PA, NP). On the phylogeny of all avian viral sequences for each segment, multiple distinct subtrees (clades) were identified that represent viral subpopulations, which are likely to have evolved within particular host taxa. Using simple regression analysis, we found that mutation rates were significantly higher in viruses infecting chickens than domestic ducks and in those infecting wild shorebirds than wild ducks. Host dependency of the substitution rate was also confirmed by Bayesian phylogenetic analysis. However, we did not find evidence that the mutation rate is higher in HP than in LP viruses. We discuss these results considering viral replication rate as the major determinant of mutation rate per unit time.